Globalisation and the Gender Earnings Gap: Evidence from Sri Lanka and Cambodia 1992-2015 - Raymond Robertson; Gladys Lopez-Acevedo; Yevgeniya Savchenko (Institute of Labor Economics (IZA), 2018)
This paper focuses on how the forces of globalisation, specifically the Multi-Fibre Arrangement (MFA), have affected women's wages in the apparel sector in developing countries. Using household and labour force surveys from Cambodia and Sri Lanka, we find large positive wage premiums and a closing of the male-female wage gap during the MFA period, but smaller premiums and a widening wage gap after the end of the MFA. Our results suggest that apparel exports continued to benefit women in developing countries post-MFA.
Keywords: F16; F63; F66; J21; J24; J30; J31; J81; L67; 330; apparel; Multi-Fibre Arrangement; textile; wages; women; working conditions